Degeneracy Resolution Capabilities of NOνA and DUNE in the Presence of Light Sterile Neutrino - Akshay Chatla; Sahithi Rudrabhatla; Bindu A. Bambah (Advances in High Energy Physics)
We investigate the implications of a sterile neutrino on the physics potential of the proposed experiment DUNE and future runs of NOνA using latest NOνA results. Using combined analysis of the disappearance and appearance data, NOνA reported preferred solutions at normal hierarchy (NH) with two degenerate best-fit points: one in the lower octant (LO) and δ13 = 1.48π and the other in higher octant (HO) and δ13 = 0.74π. Another solution of inverted hierarchy (IH), which is 0.46σ away from best fit, was also reported. We discuss chances of resolving these degeneracies in the presence of sterile neutrino.